2016
DOI: 10.1016/j.immuni.2016.09.008
|View full text |Cite|
|
Sign up to set email alerts
|

Bile Acids Control Inflammation and Metabolic Disorder through Inhibition of NLRP3 Inflammasome

Abstract: Reciprocal interactions between the metabolic system and immune cells play pivotal roles in diverse inflammatory diseases, but the underlying mechanisms remain elusive. The activation of bile acid-mediated signaling has been linked to improvement in metabolic syndromes and enhanced control of inflammation. Here, we demonstrated that bile acids inhibited NLRP3 inflammasome activation via the TGR5-cAMP-PKA axis. TGR5 bile acid receptor-induced PKA kinase activation led to the ubiquitination of NLRP3, which was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
481
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 572 publications
(503 citation statements)
references
References 51 publications
17
481
2
3
Order By: Relevance
“…A very recent report exhibited by Guo and colleagues (44) showed that opposite to our findings, bile acids conveyed an inhibitory effect on NLRP3 inflammasome activation. In this report, they demonstrated that bile acids inhibited NLRP3 inflammasome activation via the TGR5-cAMP-PKA axis, whereas our data showed that DCA triggered NLRP3 inflammasome activation through S1PR2-cathepsin B pathway, one possible explanation of the discrepancy is that bile acids may have dual regulatory effect on inflammasome activation by different mechanisms.…”
Section: Discussioncontrasting
confidence: 99%
“…A very recent report exhibited by Guo and colleagues (44) showed that opposite to our findings, bile acids conveyed an inhibitory effect on NLRP3 inflammasome activation. In this report, they demonstrated that bile acids inhibited NLRP3 inflammasome activation via the TGR5-cAMP-PKA axis, whereas our data showed that DCA triggered NLRP3 inflammasome activation through S1PR2-cathepsin B pathway, one possible explanation of the discrepancy is that bile acids may have dual regulatory effect on inflammasome activation by different mechanisms.…”
Section: Discussioncontrasting
confidence: 99%
“…TLCA or INT-777 treatment of mice subjected to LPS-induced sepsis or alum induced peritoneal inflammation significantly reduced IL-1β and IL-18 in Nlrp3 wild type mice but had no effect in Nlrp3 −/− mice. These findings suggest that bile acids place significant constraints on NLRP3 inflammasome -related inflammation (101), a finding supported by several earlier studies (90, 102). Opposite effects have been reported with chenodeoxycholic acid, which has been shown to activate the NLRP3 inflammasome in isolated macrophages as well as Kupffer cells initially sensitized to LPS(103).…”
Section: The Role Of the Inflammasome In Cholestatic Liver Injurysupporting
confidence: 84%
“…Phosphorylation of protein kinase A (PKA) was reported to be a negative regulator of NLRP inflammasomes 51) . Transmembrane G protein-coupled receptor 5 (TGR5) bile acid receptor-induced PKA activation leads to the ubiquitination of NLRP3, which is associated with the PKA-induced NLRP3 phosphorylation (Ser 291).…”
Section: Nlrp3 Inflammasome In Atherosclerosismentioning
confidence: 99%